The impact of nutritional intervention and resistance training on muscle strength and mass in healthy older adults—a comparative analysis - Ma, Yongye; Yan, Ruixiang; Li, Yueming; Li, Duanying; Sun, Xiaoning; Chen, Tao; Liu, Xingyu (Frontiers in Nutrition, 2025)
ObjectiveA growing body of evidence confirms that nutritional supplementation strategies combined with resistance training can enhance muscle strength and mass in older adults. However, the optimal supplementation approach remains unclear. This study aimed to evaluate the comparative efficacy of different nutritional interventions combined with resistance training on muscle strength and mass in healthy older adults and determine the optimal strategy.MethodsA systematic search was performed across three major biomedical databases (PubMed, Web of Science, and EMbase) to identify randomized controlled trials (RCTs) investigating the effects of nutritional supplementation combined with resistance training on muscle strength and mass in healthy older adults. A total of 19 eligible RCTs were included. The search covered literature from database inception to April 2025. Two researchers independently screened studies against predefined eligibility criteria and assessed methodological quality using the Cochrane risk-of-bias tool. Stata 18.0 was used to conduct network meta-analysis.ConclusionCompared with resistance training alone, protein supplementation combined with resistance training significantly enhanced muscle strength [Standardized Mean Difference (SMD) = 0.45, 95% confidence interval (CI): 0.20,0.69; surface under the cumulative ranking curve (SUCRA) = 98.7%] and muscle mass [Mean Difference (MD) = 0.37, 95%CI: 0.04,0.70],whereas creatine supplementation demonstrated non-significant effects on muscle strength versus training alone (SMD = 0.03, 95% CI: −0.35,0.42) but yielded the most pronounced improvement in muscle mass (MD = 2.18, 95%CI: 0.92,3.44; SUCRA = 99.9%), outperforming both protein and β-hydroxy-β-methylbutyrate (HMB) interventions, with HMB supplementation critically failing to demonstrate significant benefits for muscle strength (SMD = −0.22, 95%CI: −0.57,0.12) or mass outcomes (MD = 0.05, 95%CI: −0.33,0.44).Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251026016.